2017
DOI: 10.4014/jmb.1606.06007
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds of Potato Peel Extracts: Their Antioxidant Activity and Protection against Human Enteric Viruses

Abstract: Potato peels (PP) contain several bioactive compounds. These compounds are known to provide human health benefits, including antioxidant and antimicrobial properties. In addition, these compounds could have effects on human enteric viruses that have not yet been reported. The objective of the present study was to evaluate the phenolic composition, antioxidant properties in the acidified ethanol extract (AEE) and water extract of PP, and the antiviral effects on the inhibition of Av-05 and MS2 bacteriophages, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
2
36
2
2
Order By: Relevance
“…In another study, different concentrations of cranberry juice and cranberry proanthocyanidins were found to reduce titers of MS2 and phiX‐174 bacteriophages (Su, Howell, & D'Souza, ). Similarly, it was found that potato peel extract had an inhibitory effect on Av‐05 and MS2 bacteriophages (Silva‐BeltrÁn et al, ). It has also been demonstrated antiviral effect of P, GS, and NS in several publications (Salem & Hossain, ; X. Su & D'Souza, ; Xiaowei Su, Sangster, & D'Souza, ; Yesuf, ) but the studies focusing the interactions between these extracts and phages are quite limited.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In another study, different concentrations of cranberry juice and cranberry proanthocyanidins were found to reduce titers of MS2 and phiX‐174 bacteriophages (Su, Howell, & D'Souza, ). Similarly, it was found that potato peel extract had an inhibitory effect on Av‐05 and MS2 bacteriophages (Silva‐BeltrÁn et al, ). It has also been demonstrated antiviral effect of P, GS, and NS in several publications (Salem & Hossain, ; X. Su & D'Souza, ; Xiaowei Su, Sangster, & D'Souza, ; Yesuf, ) but the studies focusing the interactions between these extracts and phages are quite limited.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, it was found that potato peel extract had an inhibitory effect on Av-05 and MS2 bacteriophages (Silva-Beltr An et al, 2017). It has also been demonstrated antiviral effect of P, GS, and NS in several publications (Salem & Hossain, 2000;Xiaowei Su, Sangster, & D'Souza, 2011;Yesuf, 2013) but the studies focusing the interactions between these extracts and phages are quite limited.…”
Section: S Aureusmentioning
confidence: 97%
“…Adding 10% potato peel powder resulted in a decrease to 385 µg/kg, although the result was not significant. Potato peels are reported to have numerous health benefits, including anti-obesity [12], anti-protozoan [13], and antiviral properties [43]. These properties seem to be associated with peel phenolic compounds and glycoalkaloids [44].…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compounds, antioxidant and antiviral activities of extracts were evaluated in dried potato peel (dried at 45 °C for 24 h and then powdered). Absolute ethanol with 5% acetic acid (95:5 ratio) was used as an extraction solvent for 72 h, and then the samples were filtered and concentrated by freeze-drying [ 101 ].…”
Section: Fruit and Vegetable Waste (Fvw)mentioning
confidence: 99%